2018
DOI: 10.1002/jcph.1109
|View full text |Cite
|
Sign up to set email alerts
|

Primary Endpoints in Pediatric Efficacy Trials Submitted to the US FDA

Abstract: The selection of appropriate endpoints in pediatric drug development trials is a critical aspect of trial design. Given the high pediatric trial failure rate, selecting optimal trial design elements, such as the primary efficacy endpoint, is essential to ensuring increased potential for trial success. The objectives of this study were to identify the primary efficacy endpoints measured in pediatric drug development trials submitted to the US Food and Drug Administration and to relate endpoint attributes to tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…For example, in immunology, composite end points are generally the registration end point for rheumatoid arthritis (American College of Rheumatism (ACR) score), psoriasis (Psoriasis Area and Severity Index (PASI)), systemic erythematosus lupus (Systemic Erythematosus Lupus Responder Index), and ulcerative colitis (Mayo score). In pediatric diseases, there has been better success in using composite scores . Similarly, in rare diseases where the sample size in registration trials may be much smaller, composite end points (e.g., North Star Ambulatory Assessment in Duchenne Muscular Dystrophy) could be envisioned to improve the quality of information without impacting multiplicity.…”
Section: Setting Appropriate Hierarchical Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in immunology, composite end points are generally the registration end point for rheumatoid arthritis (American College of Rheumatism (ACR) score), psoriasis (Psoriasis Area and Severity Index (PASI)), systemic erythematosus lupus (Systemic Erythematosus Lupus Responder Index), and ulcerative colitis (Mayo score). In pediatric diseases, there has been better success in using composite scores . Similarly, in rare diseases where the sample size in registration trials may be much smaller, composite end points (e.g., North Star Ambulatory Assessment in Duchenne Muscular Dystrophy) could be envisioned to improve the quality of information without impacting multiplicity.…”
Section: Setting Appropriate Hierarchical Relationshipsmentioning
confidence: 99%
“…In pediatric diseases, there has been better success in using composite scores. 7 Similarly, in rare diseases where the sample size in registration trials may be much smaller, composite end points (e.g., North Star Ambulatory Assessment in Duchenne Muscular Dystrophy) 8 could be envisioned to improve the quality of information without impacting multiplicity.…”
Section: Setting Appropriate Hierarchical Relationshipsmentioning
confidence: 99%
“…Ideally, the same clinical outcomes can be used in adult and pediatric studies of the same disease, and these outcomes are sensitive and reliable in both adults and children, thus requiring relatively few children in defining PD dose‐exposure‐response relationships. Sometimes the relatively small numbers of pediatric patients available or the infrequency or variability of end‐point events make it unfeasible to incorporate the adult end point into a pediatric trial because of the sample size that would be required to achieve adequate statistical power to detect a difference . In Duchenne muscular dystrophy (DMD), age at loss of ambulation is a reliable clinical outcome that could be used in defining PD, but this becomes impractical because of the need for extended treatment times before the end point is reached.…”
Section: Extrapolation Of Clinical Outcomes As Pd End Pointsmentioning
confidence: 99%
“…Sometimes the relatively small numbers of pediatric patients available or the infrequency or variability of end-point events make it unfeasible to incorporate the adult end point into a pediatric trial because of the sample size that would be required to achieve adequate S91 statistical power to detect a difference. 28 In Duchenne muscular dystrophy (DMD), age at loss of ambulation is a reliable clinical outcome that could be used in defining PD, but this becomes impractical because of the need for extended treatment times before the end point is reached. Fortunately, natural history studies are facilitating a definition of predictive clinical end points and biomarker development.…”
Section: Extrapolation Of Clinical Outcomes As Pd End Pointsmentioning
confidence: 99%
“…Among 189 drug development trials submitted in response to BPCA written requests between 1998 and 2012, 79 (42%) failed to establish efficacy . A follow‐up survey of 234 pivotal pediatric efficacy trials submitted to FDA between 2007 and 2016 found an overall lower failure rate of 24%, although this increased to 32% in pediatric trials that were conducted separately from adult trials or 39% if pediatric endpoints were different than adult endpoints . In a more detailed look at 44 failed pediatric trials between 2007 and 2014, the FDA determined that major contributing factors included inadequate dosing, unaccounted differences between the pediatric and adult disease processes, underestimated placebo response, and study design flaws .…”
Section: Regulatory Perspectivementioning
confidence: 99%